PENYELESAIAN KREDIT MACET MELALUI PENJUALAN BENDA JAMINAN HAK TANGGUNGAN PADA PT. BANK MANDIRI (PERSERO) Tbk CABANG YOGYAKARTA - , Tulus Lestari Hanantariningsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study has the objective to determine the factors that cause the occurrence of Non-Performing loan in consumer credit agreements between the debtors and creditors and how the settlement of Non-Performing loan through the sale of debtorâs collateral which still occupied by the debtor or a third party through the State Property Office and Auction Yogyakarta. The research method in this study is juridical empirical research focuses on the field study. It used primary data that obtained through interviews with respondents and the secondary data is obtained from library materials. The data analyzed by qualitative analysis and aimed to observe and understand the truth. It resulted that: 1). The factors that cause the occurrence of Non- Performing loan in consumer credit agreements are affected by 2 (two) factors